2006
DOI: 10.1002/dc.20427
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic lumina in invasive micropapillary carcinoma of the lung

Abstract: Micropapillary carcinoma of the lung is a rare neoplasm, and several reports on micropapillary carcinoma of the lung have been presented to date. We present a case of micropapillary carcinoma of the lung here. A 75-yr-old Japanese man received the medical checkup and his chest X-ray disclosed the abnormal shadow of the lower lobe of the left lung. The histological examination of resected lung and extirpated lymph node showed the finding of micropapillary carcinoma. Some neoplastic cells of primary site contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…After 13 years, the term invasive micropapillary carcinoma of the breast was proposed by Siriaunkgul and Tavassoli. 2 This morphologic pattern was subsequently identified in tumors of other organs, such as urinary bladder in 1994, 3 colon in 2005, 4 and lung in 2006, 5 and the IMPC terminology was also adopted for those tumors.…”
mentioning
confidence: 99%
“…After 13 years, the term invasive micropapillary carcinoma of the breast was proposed by Siriaunkgul and Tavassoli. 2 This morphologic pattern was subsequently identified in tumors of other organs, such as urinary bladder in 1994, 3 colon in 2005, 4 and lung in 2006, 5 and the IMPC terminology was also adopted for those tumors.…”
mentioning
confidence: 99%
“…IMPC was firstly reported as a rare variant of invasive breast cancer by Siriaunkgul and Tavassoli in 1993 . In addition to the breast, cancers exhibiting the IMPC pattern have been reported in the lung, stomach, salivary gland, pancreas, colorectum and urinary bladder, and other sites . However, to the best of our knowledge, there are no reports about IMPC of the EGJ.…”
Section: Discussionmentioning
confidence: 98%
“…Invasive micropapillary carcinoma (IMPC) is a carcinoma composed of small papillary clusters surrounded by a clear space. IMPC has been recognized as an aggressive variant of adenocarcinoma because of the high incidence of lymphatic invasion in various organs, including the breast, lung, stomach, salivary gland, pancreas, colorectum and urinary bladder . However, pure IMPC has only reported to occur in the breast, pancreas and colon .…”
mentioning
confidence: 99%
“…Micropapillary carcinoma of the lung is a recently described entity and is characterized by small papillary tufts lacking a fibrovascular core 1,2 . This tumor pursues an aggressive clinical course because of the propensity for the metastasis into lymph nodes and pleural invasion 1–7 . Some investigators have reported that pulmonary micropapillary carcinoma is frequently associated with other subtypes of adenocarcinoma, including acinar, papillary, bronchioloalveolar, mucinous and solid patterns 1–7 .…”
mentioning
confidence: 99%
“…This tumor pursues an aggressive clinical course because of the propensity for the metastasis into lymph nodes and pleural invasion 1–7 . Some investigators have reported that pulmonary micropapillary carcinoma is frequently associated with other subtypes of adenocarcinoma, including acinar, papillary, bronchioloalveolar, mucinous and solid patterns 1–7 . In contrast, cases of papillary adenocarcinoma of the lung reported by some investigators contain micropapillary carcinoma 8,9 .…”
mentioning
confidence: 99%